Hedges in English and Arabic Metadiscourse Utility in Academic Writing: A Contrastive Analysis - Kheryadi, Kheryadi; Muin, Abdul; Syahid, Ahmad Habibi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
This current study has increased the amount of studies on metadiscourse features in English and Arabic, as well as cultural groupings, by examining the usage of hedging in linguistic research articles published in English and Arabic. The technique was qualitative, with a corpus of 40 articles from six linguistics journals used. This study aimed to identify similarities and differences in the use of hedges in native English and native Arabic linguistics research publications. Hyland's taxonomy of metadiscourse markers was used to analyze the language categories. The contrastive analysis of English and Arabic in this article was a systematic investigation of language pairs to uncover differences and similarities. Arabic articles are not more dominant than English articles in the Hidges structure. The result showed that hedges in English is greater than in Arabic research articles. From those findings, it might have a substantial influence on the teaching and learning of Arabic as a foreign language in English context.